Kompleksnaja ocenka podgotovlennosti kvalificirovannyh sportsmenok v hudozhestvennoj gimnastike - Shynkaruk, O.; Topol, A. (Science in Olympic Sport, 2017)
The paper examines the issue of monitoring athletes` preparedness in complex coordination sports and rhythmic gymnastics. Significant indicators and tests for assessing athletes` preparedness in rhythmic gymnastics are identified. We have substantiated an approach to and developed an algorithm to control the preparedness of gymnasts specializing in group exercises. An integrated assessment of the preparedness of gymnasts in group exercises was developed. The developed integrated assessment of the kinds of preparedness of gymnasts in group exercises allows to characterize athlete`s capabilities in integral criteria, to identify strong and weak sides of their preparation to manage their training process, to report test results as a score, to compare the obtained results with the standards, to calculate the final score of preparedness taking into account the technique of competitive compositions in the team and individual characteristics of gymnasts that determine the athletic performance.